Top prospect - Volponi, Paul (Carolrhoda Books, 2016)
When football prodigy Travis Gardner's older brother gets a spot on the Gainesville University team, the coach offers Travis a spot too, once he finishes high school. In the face of sudden fame, Travis must prove himself among jealous teammates and vicious opponents.